2018
DOI: 10.1017/9781108555883
|View full text |Cite
|
Sign up to set email alerts
|

Climate, Clothing, and Agriculture in Prehistory

Abstract: CLIMATE CHANGE AND THE INVENTION OF CLOTHES T he human need for clothes did not start out from any sense of modesty nor a desire to decorate ourselves: naked hunter-gatherers, such as the Australian Aborigines, can easily disprove those theories. This is likewise for theories of clothing origins that are based on social purposes, such as displaying social roles. Of course, these motivesmodesty and displayare often the main reason why we wear clothes in the modern world. And, like a lot of modern things, they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 595 publications
0
19
0
Order By: Relevance
“…Proxies such as faunal remains at hominin sites can give an indication as to what type of clothing Neanderthals may have made. One such study concluded that H. sapiens developed more complex clothing than Neanderthals, the latter of which produced comparatively simple garments likened to fur capes (Collard et al ., ; see Gilligan, , for more information on simple and complex clothing).…”
Section: Technological Buffering and Optimizationmentioning
confidence: 99%
“…Proxies such as faunal remains at hominin sites can give an indication as to what type of clothing Neanderthals may have made. One such study concluded that H. sapiens developed more complex clothing than Neanderthals, the latter of which produced comparatively simple garments likened to fur capes (Collard et al ., ; see Gilligan, , for more information on simple and complex clothing).…”
Section: Technological Buffering and Optimizationmentioning
confidence: 99%
“…Thus, the trade-off for "ancient" MtbC lineages is the higher probability of progression to active TB at a cost of being less able to disseminate through the population explaining why "ancient" lineages can only be found in certain geographical locations 21 . The fact that the appearance of "modern" lineages (46,000 BCE) coincided with a significant increase in the population (from 10 4 to 10 6 individuals) in Asia, while remaining constant in Africa (around 10 6 people) 22,23 , indicates that some sort of population explosion occurred in Asia before the Neolithic, as proposed by several authors [24][25][26] , giving support to its dissemination.…”
mentioning
confidence: 71%
“…There is a wide consensus regarding the stability of the population density in the Middle Paleolithic. Thus, it appears that the growth rate was around 0.003%, which significantly increased up to the 0.1% in the Neolithic 13,26,52 . We have adjusted this rate for the expected predominant lineage in each period, namely the "ancient" one for the Paleolithic and the "modern" for the Neolithic, to determine the birth rate (λ).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Such research also highlights the ways that archaeology is uniquely positioned to register the degree to which humans have shaped themselves as they have created the current world, providing lessons for more sustainable ecologies and more balanced renderings of the intertwined human and natural actions that constitute environmental history (d'Alpoim Guedes and Hein ; Garcin et al. ; Gilligan ; Kintigh and Ingram ; Malhi ; Sanchez et al. ; Snitker ).…”
Section: Socionature and Political Ecologymentioning
confidence: 99%